3D human reconstruction - Gucon, Nailah Ginylle Pabilonia (Nanyang Technological University, 2023)
The human brain's remarkable ability to transform a two-dimensional image into a vivid three-dimensional representation of a person highlights the brain's remarkable capabilities. Nonetheless, translating this extraordinary human capacity into machine learning models, specifically deep neural networks, for the purpose of “3D Human Reconstruction from a Single Image”, poses a substantial and intricate challenge.